Altered Platelet Shape Change in Hereditary Gelsolin Asp187Asn-related Amyloidosis - Kiuru, Sari; Javela, Kaija; Somer, Hannu; Kekomäki, Riitta (Thrombosis and Haemostasis, 2000)
Hereditary gelsolin-related amyloidosis (AGel amyloidosis) is a systemic disorder caused by a G654A or G654T mutation in the gene coding for gelsolin, an actin-modulating protein. Altered platelet shape change has been demonstrated in gelsolin-deficient knock-out mice, but this has not been studied in humans with gelsolin deficiency. We measured platelet shape change, characterized by maximal decrease in light transmission (D) and reaction time (T), and aggregation, associated with stimulation of platelets with different agonists in platelet rich plasma, as well as coagulation factor VIII and ristocetin cofactor activities in 20 patients, 10 healthy sibs and 20 healthy control subjects. Statistically significant alterations of parameters describing platelet shape change (D, T) were observed after stimulation with adenosine diphosphate and collagen in patients when compared to healthy subjects, but not in maximal aggregation responses, platelet counts, coagulation factor VIII or ristocetin cofactor activity levels. Patients had more haemostatic derangements. Our results suggest that, in addition to amyloid deposition, the G654A gelsolin gene defect causes altered gelsolin-mediated cellular mechanisms, which may contribute, e. g., to bleeding tendency in AGel amyloidosis patients.
Keywords: Aggregometry; gelsolin; hereditary gelsolin-related amyloidosis; platelet shape change; platelet function